The king of limbs [compact disc] (Ticker Tape Ltd : TBD Records, 2011)
Radiohead's much-anticipated eighth studio album is the follow-up to their seven-time Grammy-nominated In Rainbows. Produced by longtime collaborator Nigel Godrich. The King of Limbs, named after a spooky tree in Wiltshire's Savernake Forest, has a somber sound. The song Codex is a beautiful piano ballad with string arrangements performed by the London Telefilmonic Orchestra.